2015
DOI: 10.1093/mnras/stv2726
|View full text |Cite
|
Sign up to set email alerts
|

Helicity inversion in spherical convection as a means for equatorward dynamo wave propagation

Abstract: We discuss here a purely hydrodynamical mechanism to invert the sign of the kinetic helicity, which plays a key role in determining the direction of propagation of cyclical magnetism in most models of dynamo action by rotating convection. Such propagation provides a prominent, and puzzling constraint on dynamo models. In the Sun, active regions emerge first at mid-latitudes, then appear nearer the equator over the course of a cycle, but most previous global-scale dynamo simulations have exhibited poleward prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 62 publications
(88 reference statements)
7
43
0
Order By: Relevance
“…Including an α-effect also concentrated at lower latitudes produces equatorward cycles with shorter cycle periods with the strongest magnetic fields appearing at lower latitudes. These results are in qualitative agreement with direct and largeeddy simulations (Käpylä et al 2012(Käpylä et al , 2013bAugustson et al 2015; Duarte et al 2016). …”
Section: Varying Latitudinal η T Profilesupporting
confidence: 88%
See 1 more Smart Citation
“…Including an α-effect also concentrated at lower latitudes produces equatorward cycles with shorter cycle periods with the strongest magnetic fields appearing at lower latitudes. These results are in qualitative agreement with direct and largeeddy simulations (Käpylä et al 2012(Käpylä et al , 2013bAugustson et al 2015; Duarte et al 2016). …”
Section: Varying Latitudinal η T Profilesupporting
confidence: 88%
“…It is now believed that the equatorward migration in the simulations is facilitated by a region of negative shear and positive (negative) α effect in the northern (southern) hemisphere -in accordance with the ParkerYoshimura rule (Warnecke et al 2014). Recently an alternative scenario was reported by Duarte et al (2016), who found that the sign of the α effect can be inverted in certain parameter ranges allowing equatorward migration also with positive radial shear. Although it is unclear to what extent those simulations represent stellar magnetic fields, it might be helpful to understand first the mechanism operating in those simulations before trying to understand real stars.…”
Section: Introductionmentioning
confidence: 61%
“…It is remarkable that this rule also seems to apply to the fully nonlinear convective dynamo simulations (Warnecke et al , 2016b. The current simulations can produce equatorward migration only in cases where a region with a negative radial gradient of Ω occurs at mid-latitudes (e.g., Käpylä et al 2012Käpylä et al , 2013Augustson et al 2015) or if the sign of the kinetic helicity, which is a proxy of the α effect, is inverted in the bulk of the convection zone (Duarte et al 2016).…”
Section: Differential Rotation and Meridional Circulationmentioning
confidence: 95%
“…In such models, the product of α and ∂Ω/∂r must therefore be negative in the northern hemisphere in order to obtain an equatorward butterfly diagram. As noted above, the sign of α is related to that of the kinetic helicity, H k = v · (∇ × v), and H k in turn is typically negative in the northern hemisphere owing to the properties of the rotating convection (but see discussion in, e.g., Duarte et al 2015, who point out circumstances where the opposite sign may prevail). One problem arose when helioseismology revealed that the differential rotation profile was nearly conical at mid-latitudes (e.g., Thompson et al 1996), i.e.…”
Section: Overview Of Mean Field Modelsmentioning
confidence: 95%